Preceptor preferences for participating in electronic preceptor development - Medina MS; Ray NE; Davison M (Centro de Investigaciones y Publicaciones Farmaceuticas, 2009)
Objectives: New guidelines require preceptors to deliver approximately 30% of the doctor of pharmacy curricula. With preceptor's increasing responsibilities, colleges are faced with the task of training preceptors as educators. Identifying preceptor's training format preferences (i.e. electronic vs. live) should contribute to the more effective and efficient creation of training materials and programs. Methods: A preceptor training video was created and made available electronically and was distributed to 400 preceptors with a brief 2-part questionnaire about preceptor training preferences, electronic training preferences after viewing the video, and available technology resources for participating in electronic training.Results: 38.25% of the questionnaires were returned. The majority of respondents (57%) preferred electronic to live preceptor developing training and the majority (53%) had not previously attended the live annual preceptor development conference offered by the college. 51.6% participants reviewed the electronic training video created by the OU College of Pharmacy. Of the respondents who did not watch the video, 73% cited having too little time, problems accessing the video, or technical reasons for not watching the training video. The majority of responders in all age groups preferred electronic training to face-to-face training except those ages 61-65 and the majority (55.7%) would participate in on-line training again in the future. The majority of respondents have the technical resources to participate in electronic training. Conclusion: Preceptors have limited time to participate in preceptor development training, although they view training as an important activity. This study reveals three main findings: (1) the majority of preceptors prefer electronic preceptor development training programs regardless of age; (2) would participate in future electronic training after having participated in electronic training; and (3) have the available resources to participate in electronic training. Future preceptor development programs should have flexible formats to accommodate preferences for live and electronic programming.